Qui a bâti Bruxelles ? Profil des artisans et entrepreneurs du secteur bruxellois de la construction vers 1865 - Matthijs Degraeve (Brussels Studies, 2024)
Around 1865, Brussels was undergoing a profound transformation. Recent research has offered insight into the roles of various stakeholders in the growth of the city, such as government bodies and landowners. However, little is yet known about the craftspeople and construction entrepreneurs who physically shaped the city. Through almanacs, patent registers, electoral rolls and land registers, this article sheds light on the professional, socio-demographic and spatial profile of 2 445 businesses in the Brussels construction sector around 1865. It reveals a highly heterogeneous group who were active in various building professions. Whereas a few wealthy entrepreneurs led large companies, the labour-intensive, small-scale organisation of most construction companies meant that entrepreneurship was also open to a large group of craftspeople of relatively modest means, including women and newcomers. This also led to a wide spatial distribution, due to which construction companies could work on sites in their own neighbourhoods. The results contribute to historical knowledge of how the urban fabric and heritage of Brussels were created and also put today’s need for the urban construction sector to be locally embedded into a long-term perspective.